Work-Life Balance and its Impact on Turnover Intention in the Millennium: the Mediation Role of Job Satisfaction - Sahidillah Nurdin; Heni Rohaeni (Universitas Medan Area, 2020)
This research is motivated by the demographic bonus of the productive age faced by Indonesia. The purpose of this study was to determine how much influence and the contribution of work-life balance to intention turnover in millennial generation mediated by job satisfaction. The population in this study is the millennial generation who work in companies in the city of Bandung, male and female aged between 20-38 years, the sample used in this study amounted to 97 respondents. Data collection techniques using questionnaires distributed to respondents with nonprobability sampling sampling techniques. The data analysis tool used is SEM (Structural Equation Modeling) using a statistical data processing tool Smart-PLS. The results showed that work-life balance has a significant effect on job satisfaction, job satisfaction has a significant effect on intention turnover, but work-life balance has no significant effect on intention turnover, job satisfaction is able to mediate the influence of work life balance on intention turnover significantly